A CFD simulation study on pressure drop and velocity across single flow microchannel heat sink - Sadikin, Azmah; Razali, A. A. (Penerbit Akademia Baru, 2015)
This paper presents a numerical simulation of flow in a microchannel heat sink. The channel was defined as a dimension with less than 1.0milimeter and greater than 100.0micrometer. The ANSYS CFX 2015 was used to predict the flow in the microchannel. Besides, simulations were undertaken to determine the flow of the fluid within the microchannel in three different models. Therefore, three different models were employed for this study. The first model was a square-shaped channel with 0.5mm width and 0.5mm height constructed along 28.0mm channel length. The second and the third models were in rectangular shape. The differences between these models were their width and height of channel. The dimension for the second model was 0.75mm height and 0.5mm width (rectangular A), while the dimension for the third model was 0.5mm height and 0.75mm width (rectangular B). All the microchannel heat sink models had been simulated and showed results for pressure, temperature, and velocity inside the microchannel. The results were compared for each model and the data had been validated from published data. In addition, the initial velocity was set in a range between 0.1m/s and 0.5m/s. The highest pressure drop was recorded for the square microchannel. It was 58.12% higher than the pressure drop found in the rectangular microchannel with 0.75mm width, while 0.02% closer with the 0.75mm-height rectangular microchannel. Furthermore, there was a 33.34% of temperature difference, which had been higher for the square microchannel. Nevertheless, the highest velocity of 0.57m/s was recorded at the outlet of the microchannel. These had been consistent with other published data"